Rhizospheric microbial consortium of Lilium lancifolium Thunb. causes lily root rot under continuous cropping system - Dai, Liangliang; Singh, Sunil K.; Gong, Hao; Tang, Yuanyuan; Peng, Zhigang; Zhang, Jun; Wu, Dousheng; Zhang, Huiming; He, Danxia (Frontiers in Microbiology, 2022)
Tiger lily (Lilium lancifolium Thunb.) is a cash crop with a long history of cultivation in China. Its roots have long been used as a valuable component of Chinese medicine. Continuous cropping, the conventional planting approach for tiger lily, often leads to severe root rot disease, but it is not yet clear how this planting method leads to root rot. In this study, we analyzed the rhizosphere microbiome and predicted microbial protein function in tiger lily planted with the continuous cropping method in three different geological types of soil. In order to explore the specific rhizosphere microbiota triggering root rot disease, tiger lily was compared to maize grown in a similar system, which showed no disease development. An analysis of the chemical elements in the soil revealed that the Pseudomonas and Streptomyces genera, with pathogenic functions, were dominant in the tiger lily rhizosphere. The lower soil pH of tiger lily compared to maize supports the accumulation of pathogenic bacteria in the tiger lily rhizosphere. Meanwhile, we discovered that bacteria of the Flavobacterium genus, with their predicted phosphate transport function, specifically accumulated in the maize rhizosphere. Our findings suggest that Pseudomonas and Streptomyces bacteria may result in continuous cropping–induced root rot disease in tiger lily and that Flavobacterium could serve to protect maize from pathogenic bacteria.